Factors Related to the Prevention of Influenza among Female High School Students in Hamedan: Application of Protection Motivation Theory - Mohadeseh Sadri; Majid Barati; Saeid Bashirian; Salman Khazaei; Ensiyeh Jenabi; Alireza Soltanian; Elaheh Ezati; Sasan Navkhasi (Hamadan University of Medical Sciences, 2024)
Background and Objective: Influenza is one of the most common infectious diseases in the respiratory system. Preventive measures are considered one of the most important and necessary strategies to control this disease. The present study aimed to assess the factors related to the prevention of influenza among female high school students based on the protection motivation theory in Hamedan. Materials and Methods: This cross-sectional study was conducted on 303 female high school students in Hamadan. The participants were selected by multistage sampling. The data collection tool was a questionnaire designed by Sharifi-Rad et al. and completed by the self-reporting method. Data were analyzed using independent t-tests, one-way analysis of variance, Pearson correlation, and linear regression with a significance level of less than 0.05. Results: The mean age of participants in the research was 16.79±0.95 years. Only 26.10% of participants had a history of influenza vaccination. Moreover, 186 cases had information about the flu, and the Internet was identified as the most abundant source of information. Based on the results, the various constructs of protection motivation theory explained 58.30% of the variance of the intention to perform preventive behavior and 30.30% of the variance of performing the behavior in the studied students. Conclusion: In conclusion, the various constructs of the protection motivation theory have a good fit for predicting the intention and performing disease-preventive behaviors.